2016
DOI: 10.1515/pjvs-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status of blood and liver of turkeys fed diets enriched with polyunsaturated fatty acids and fruit pomaces as a source of polyphenols

Abstract: It was hypothesized that dietary polyphenol-rich fruit pomaces can improve the antioxidant status of both diets and the tissues of turkeys fed such diets. Turkeys were fed diets containing a cellulose preparation (C) or 5% dried apple pomace (AP), blackcurrant pomace (BCP), strawberry pomace (SP) and seedless strawberry pomace (SSP). Blood and liver biochemical parameters were determined in 7 birds from each experimental group slaughtered at 15 weeks of age, after 5 weeks of feeding diets containing soybean oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…As a consequence, if the redox status is not maintained, an imbalance between production and destruction of reactive oxygen species (ROS) occurred producing oxidative stress. Fruit pomaces seemed to be a promising natural source of antioxidant compounds as reported by Jankowski et al [9]. In their study, they observed beneficial effects on blood antioxidant parameters in turkeys fed diets supplemented with apple, strawberry or blackcurrant pomace in terms of increased vitamin C concentration, integral antioxidant capacity of lipophilic and hydrophilic substances and decreased lipid peroxide levels.…”
Section: Introductionmentioning
confidence: 70%
“…As a consequence, if the redox status is not maintained, an imbalance between production and destruction of reactive oxygen species (ROS) occurred producing oxidative stress. Fruit pomaces seemed to be a promising natural source of antioxidant compounds as reported by Jankowski et al [9]. In their study, they observed beneficial effects on blood antioxidant parameters in turkeys fed diets supplemented with apple, strawberry or blackcurrant pomace in terms of increased vitamin C concentration, integral antioxidant capacity of lipophilic and hydrophilic substances and decreased lipid peroxide levels.…”
Section: Introductionmentioning
confidence: 70%
“…Moreover, our data did not show significant differences in TAC of muscle tissue extracts. An explanation could be that the role of vitamin E on the tissue depends on the age of the birds (Jankowski et al, 2016). To investigate the specific issue, studies at earlier ages of birds would have to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no difference in ACW, although a trend towards a higher value was noticed in group +C. Jakowski et al ( 2016 ) exposed that turkeys fed diets enriched with different antioxidant supplements showed a change in the level of ACW in plasma, and so additional research on this topic should be carried out.…”
Section: Discussionmentioning
confidence: 99%